Piezoelectric laminated film and method for producing the same

JP7629988B2Active Publication Date: 2025-02-14KUREHA CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023517228
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-28
Filing Date
2022-04-04
Publication Date
2025-02-14
Estimated Expiration
2042-04-04

AI Technical Summary

Benefits of technology

【0011】 本発明の一態様によれば、高温高湿環境下において色調が悪化しない、位置センサと押圧検出センサとの積層体を実現することできる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629988000001
    Figure 0007629988000001
  • Figure 0007629988000002
    Figure 0007629988000002
  • Figure 0007629988000003
    Figure 0007629988000003
Patent Text Reader

Abstract

Provided is a piezoelectric laminated film that is not discolored in high-temperature, high-humidity environments. This piezoelectric laminated film is configured from a piezoelectric film and a transparent adhesive film that satisfies condition 1. Condition 1: When a volatile component obtained from a test piece measuring about 1 cm2 upon being held for 90 minutes at 85°C is subjected to solid-phase microextraction, caused to adsorb to fibers coated with polydimethylsiloxane, and analyzed through gas chromatograph mass spectrometry, the total amount of organic matter detected within a three-minute retention time is 50 μg in terms of the weight of 2,2'-azobis(isobutyronitrile).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a piezoelectric laminate film and a method for producing the piezoelectric laminate film. [Background technology]

[0002] Touch panel technology that simultaneously detects position and pressure has been attracting attention. As a means of realizing this, Patent Document 1 discloses a method of stacking a conventional capacitive position detection sensor and a pressure detection sensor including a piezoelectric film. As disclosed in Patent Document 2, these position detection sensor and pressure detection sensor are stacked, and each layer is adhered by a transparent adhesive sheet. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2013 / 021835 [Patent Document 2] International Publication No. 2015 / 156196 Summary of the Invention [Problem to be solved by the invention]

[0004] One of the uses of touch panels is in automotive touch panels. It is known that the electronic components of automotive touch panels are required to have high environmental resistance. For example, the performance of the touch panel must not deteriorate and it must function normally even if it is left for a long time in a high-temperature and high-humidity environment of 85°C and 85% RH.

[0005] However, as a result of investigations carried out by the present inventors, it was found that a laminate of a conventional position detection sensor and a pressure detection sensor including a piezoelectric film has a problem in that the color tone deteriorates in a high-temperature and high-humidity environment.

[0006] SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide a laminate of a position sensor and a pressure detection sensor, the color of which does not deteriorate in a high-temperature, high-humidity environment. [Means for solving the problem]

[0007] In order to solve the above problems, a piezoelectric laminate film according to one embodiment of the present invention is a piezoelectric laminate film that is composed of a piezoelectric film and a transparent adhesive sheet, and the transparent adhesive sheet is a transparent adhesive sheet that satisfies the following condition 1.

[0008] Condition 1: 1cm when held at 85℃ for 90 minutes 2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the total amount of organic matter detected after a retention time of 3 minutes was 50 μg or less in terms of weight of 2,2'-azobis(isobutyronitrile).

[0009] Furthermore, a method for producing a piezoelectric laminate film according to one embodiment of the present invention is a method for producing a piezoelectric laminate film, including a preparation step of preparing a transparent adhesive sheet that satisfies the following condition 1, and a lamination step of laminating the transparent adhesive sheet that satisfies the condition 1 and a piezoelectric film.

[0010] Condition 1: 1cm when held at 85℃ for 90 minutes 2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the total amount of organic matter detected after a retention time of 3 minutes was 50 μg or less in terms of weight of 2,2'-azobis(isobutyronitrile). Effect of the Invention

[0011] According to one aspect of the present invention, it is possible to realize a laminate of a position sensor and a pressure detection sensor, the color tone of which does not deteriorate in a high-temperature and high-humidity environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, one embodiment of the present invention will be described in detail.

[0013] [1. Piezoelectric laminated film] A piezoelectric laminate film according to one embodiment of the present invention is composed of a piezoelectric film and a transparent adhesive sheet, and the transparent adhesive sheet is a transparent adhesive sheet that satisfies the following condition 1.

[0014] Condition 1: 1cm when held at 85℃ for 90 minutes 2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the total amount of organic matter detected after a retention time of 3 minutes was 50 μg or less in terms of weight of 2,2'-azobis(isobutyronitrile).

[0015] The term "piezoelectric film" refers to a film having piezoelectricity. The transparent adhesive sheet is not particularly limited, but may be, for example, a sheet material having optical properties that transmit 90% or more of visible light and further having adhesive properties. As the transparent adhesive sheet, a commercially available one may be used, as described later.

[0016] Detailed conditions such as the equipment used in Condition 1 may be changed as appropriate as long as similar measurement results are obtained.

[0017] In condition 1, all the equipment used for performing solid-phase microextraction is for an autosampler. The fiber may be coated with polydimethylsiloxane. The coating preferably has a thickness of 5 μm or more, more preferably 10 μm or more, even more preferably 50 μm or more, and most preferably 80 μm or more. Furthermore, the coating most preferably has a thickness of 125 μm or less. By being within this range, the volatile components of the transparent adhesive sheet can be detected. For example, the coating may have a thickness of 100 μm.

[0018] The length of the coated portion of the fiber is preferably 0.5 cm or more, and more preferably 1 cm or more. Furthermore, the length of the coated portion is preferably 3 cm or less, and more preferably 2 cm or less. When the length of the coated portion of the fiber is within this range, measurement with sufficient detection sensitivity is possible.

[0019] In condition 1, the holder used for solid-phase microextraction may be one for an autosampler into which the above-mentioned fiber can be inserted.

[0020] The gas chromatograph mass spectrometer is not particularly limited as long as it is compatible with solid phase microextraction. For example, the gas chromatograph mass spectrometer may be Agilent GC7890A / MS5975C, Shimadzu QP2020, or JEOL JMS-1500GC.

[0021] The column used in the gas chromatograph is not particularly limited as long as it is a capillary column of medium polarity.

[0022] The ionization method used in mass spectrometry is EI (Electron Ionization).

[0023] 2,2'-azobis(isobutyronitrile) is a component that is widely contained in transparent adhesive sheets. By converting the amount of 2,2'-azobis(isobutyronitrile) contained in the transparent adhesive sheet into a weight conversion, it becomes possible to evaluate a wide range of transparent adhesive sheets.

[0024] As a result of the inventors' investigations, they found that when a piezoelectric film is exposed to the volatile components of a transparent adhesive sheet in a high-temperature, high-humidity environment, the volatile components react with the piezoelectric film, causing a change in color tone of the piezoelectric film. By using a transparent adhesive sheet that satisfies the above condition 1 for the piezoelectric laminate film, the amount of volatile components in a high-temperature, high-humidity environment can be reduced to an extremely small amount, making it possible to suppress color tone change of the piezoelectric film in a high-temperature, high-humidity environment. The color tone of the piezoelectric laminate film can be reduced by a * Value, b * Value, L * It can be evaluated by value.

[0025] When an analysis similar to that under condition 1 above is performed, the total amount of organic matter detected after a retention time of 3 minutes is 30 μg or less, more preferably 10 μg or less, calculated as 2,2'-azobis(isobutyronitrile) by weight, thereby making it possible to suitably suppress color change in the piezoelectric film.

[0026] Volatile components of the transparent adhesive sheet that change the color tone of the piezoelectric film include organic substances, which will be described later, particularly acidic compounds, basic compounds, and silane coupling agents.

[0027] In the piezoelectric laminate film according to one embodiment of the present invention, the transparent adhesive sheet may be a transparent adhesive sheet which further satisfies the following condition 2.

[0028] Condition 2: 1cm when held at 85℃ for 90 minutes 2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the amount of components attributed to bases and silane coupling agents detected after a retention time of 3 minutes was less than 15 μg, calculated as 2,2'-azobis(isobutyronitrile) by weight.

[0029] Examples of volatile components of the transparent adhesive sheet that cause changes in the color tone of the film include bases and silane coupling agents. It is preferable to use a transparent adhesive sheet that satisfies the above condition 2, since the amounts of these components can be limited.

[0030] When the same analysis as in Condition 2 is performed, the amount of components belonging to the base and the silane coupling agent detected after a retention time of 3 minutes is preferably 15 μg or less, more preferably 10 μg or less, and even more preferably 5 μg or less, calculated as 2,2'-azobis(isobutyronitrile) by weight. When the amount of the components belonging to the base or the silane coupling agent is within the range, the color tone change of the piezoelectric film can be suitably suppressed.

[0031] In the piezoelectric laminate film according to one embodiment of the present invention, the transparent adhesive sheet may be a transparent adhesive sheet which further satisfies the following condition 3.

[0032] Condition 3: 1 cm when held at 85°C for 90 minutes 2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the amount of components belonging to acidic compounds detected after a retention time of 3 minutes was less than 20 μg, calculated as 2,2'-azobis(isobutyronitrile) by weight.

[0033] When the same analysis as in Condition 3 is performed, the amount of components belonging to acidic compounds detected after a retention time of 3 minutes is preferably 15 μg or less, more preferably 10 μg or less, and even more preferably 5 μg or less, calculated as 2,2'-azobis(isobutyronitrile) by weight. When the amount of components belonging to acidic compounds is within this range, color tone changes in the piezoelectric film can be suitably suppressed.

[0034] The acidic compounds volatilized from the transparent pressure-sensitive adhesive sheet may be evaluated by a method other than the above-mentioned evaluation method. For example, the acid value of the volatile components may be evaluated by a method conforming to JIS K0070-1992.

[0035] In addition, in conditions 1 to 3, the amount of the volatile components measured is preferably as small as possible, since this makes it possible to suppress changes in color tone of the piezoelectric film.

[0036] Here, examples of the volatile components of the transparent adhesive sheet include acidic compounds, basic compounds, and silane coupling agents. Specific examples of the volatile components of the transparent adhesive sheet are given below, but even if the compounds are not listed below, they are included as volatile components as long as they are detected as volatile components of the transparent adhesive sheet by the detection methods described in the above conditions 1, 2, and 3.

[0037] Examples of the acidic compound include unsaturated carboxylic acid compounds and unsaturated dicarboxylic acid compounds, etc. More specifically, examples of the acidic compound include acrylic acid, methacrylic acid, maleic acid, and fumaric acid.

[0038] Examples of the basic compound include amide compounds, amino compounds, hydroxyl group-containing amino compounds, and hydroxyl group-containing amide compounds. More specific examples include N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, imidazole, N,N-dimethylacrylamide, 2-(dimethylamino)ethyl acrylate, N-methylolacrylamide, and N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine.

[0039] Silane coupling agents are compounds in which hydrolyzable groups and reactive functional groups are bonded to silicon atoms. The hydrolyzable groups of silane coupling agents are not particularly limited, but include, for example, methoxy groups, ethoxy groups, and dialkoxy groups. The reactive functional groups of silane coupling agents are not particularly limited, but include, for example, vinyl groups, epoxy groups, styryl groups, methacryl groups, acrylic groups, amino groups, isocyanurate groups, ureido groups, mercapto groups, and isocyanate groups as functional groups of silane coupling agents. The combination of hydrolyzable groups and reactive functional groups of silane coupling agents is not particularly limited.

[0040] Examples of such silane coupling agents include those described in JP 2020-143242 A. Typical examples include 3-glycidyloxypropyltrimethoxysilane and trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane.

[0041] (Transparent adhesive sheet) The transparent adhesive sheet is not particularly limited in type and manufacturing method as long as it satisfies the above-mentioned condition 1 or both conditions 1 and 2 and has the function of bonding layers as a transparent adhesive sheet. The transparent adhesive sheet may be configured by applying an adhesive to both sides of a substrate, or may be configured only with an adhesive layer as a substrate-less transparent adhesive sheet that does not include a substrate. From the viewpoint of thinning, a substrate-less transparent adhesive sheet is more preferable. The thickness of the transparent adhesive sheet is preferably 5 μm or more, and more preferably 10 μm or more. If the thickness of the transparent adhesive sheet is thinner than the range, problems occur in the step followability. In addition, the thickness of the transparent adhesive sheet is preferably 2000 μm or less, more preferably 125 μm or less, even more preferably 80 μm or less, and particularly preferably 50 μm or less. If the thickness of the transparent adhesive sheet is thicker than the range, the sensitivity as a touch panel decreases.

[0042] For example, a commercially available transparent adhesive sheet may be used as the transparent adhesive sheet. Note that even if a commercially available transparent adhesive sheet does not satisfy the above-mentioned condition 1 or conditions 1 and 2, it may be used after a preparation step of carrying out any processing to prepare a transparent adhesive sheet that satisfies the conditions. Details of the preparation step of the transparent adhesive sheet will be described later in [2. Manufacturing method of piezoelectric laminate film].

[0043] The material of the transparent adhesive sheet can be selected from any material that can be used for a transparent laminate film. The material may be an inorganic material or an organic material, and may be one or more types. Examples of the material include acrylic resin-based adhesives, rubber-based adhesives, silicone-based adhesives, polyester-based adhesives, polyurethane-based adhesives, polyamide-based adhesives, epoxy resin-based adhesives, polyvinyl alkyl ether-based adhesives, and fluororesin-based adhesives. Among them, acrylic resin-based adhesives are superior in terms of cost-effectiveness and thin film formation.

[0044] (Piezoelectric film) The type of piezoelectric film is not particularly limited, and examples thereof include films containing, as a main component, any of the following: fluorine-based resins, vinylidene cyanide polymers, odd-numbered nylons such as nylon 9 and nylon 11, helical chiral polymers such as polylactic acid, polyhydroxycarboxylic acids such as polyhydroxybutyrate, cellulose derivatives, polyurea, and mixtures of ceramic piezoelectric bodies and resins.

[0045] In particular, the piezoelectric film may contain a fluororesin as a main component. Here, "containing a fluororesin as a main component" means that the content of any resin contained in the piezoelectric resin composition may be 51% by mass or more, 80% by mass or more, or 100% by mass.

[0046] The fluororesin may be any fluororesin usable in the piezoelectric film, and may be one or more of such fluororesins, examples of which include polyvinylidene fluoride resin, tetrafluoroethylene resin, and mixtures thereof.

[0047] Examples of vinylidene fluoride resins include homopolymers of vinylidene fluoride and copolymers thereof. The content of constituent units derived from monomers other than vinylidene fluoride in the copolymers of vinylidene fluoride may be appropriately determined within a range that allows the piezoelectric laminate film to exhibit characteristics according to its intended use.

[0048] Examples of the monomer other than vinylidene fluoride in the copolymer of vinylidene fluoride include hydrocarbon monomers and fluorine compounds. Examples of the hydrocarbon monomer include ethylene and propylene. The fluorine compound is a fluorine compound other than vinylidene fluoride, and has a polymerizable structure. Examples of the fluorine compound include vinyl fluoride, trifluoroethylene, trifluorochloroethylene, tetrafluoroethylene, hexafluoropropylene, and fluoroalkyl vinyl ether.

[0049] Examples of tetrafluoroethylene resins include homopolymers of tetrafluoroethylene and copolymers thereof. Examples of monomers other than tetrafluoroethylene that constitute the structural units of the copolymers include ethylene, fluoropropylene, fluoroalkylvinylether, perfluoroalkylvinylether, and perfluorodioxysol.

[0050] The piezoelectric film of the present embodiment may contain various additives within the range in which the effects of the present embodiment can be obtained. The additives may be one or more kinds, and examples thereof include plasticizers, lubricants, crosslinking agents, UV absorbers, pH adjusters, stabilizers, antioxidants, surfactants, and pigments.

[0051] The thickness of the piezoelectric film is preferably 5 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, from the viewpoint of fully expressing the piezoelectricity and mechanical strength. The thickness of the piezoelectric film is preferably 200 μm or less, more preferably 120 μm or less, and even more preferably 80 μm or less, from the viewpoint of fully expressing the transparency and piezoelectricity. The thickness of the laminated film can be determined according to a known method, for example, by observing the cross section of the laminated film.

[0052] The piezoelectric properties of the piezoelectric film in this embodiment can be appropriately determined within a range in which the effects of this embodiment can be obtained, depending on the application of the piezoelectric laminate film. If the piezoelectric properties of the piezoelectric laminate film are too low, the function as a piezoelectric material may be insufficient. From the viewpoint of exhibiting sufficient piezoelectric properties, for example, when the piezoelectric laminate film is used in a touch panel, the piezoelectric properties of the piezoelectric film are set to a value of 0.01 to 0.015, where d 33 The piezoelectric constant d is preferably 6 pC / N or more, more preferably 10 pC / N or more, and even more preferably 12 pC / N or more. There is no upper limit to the piezoelectric characteristic, but in the above case, from the viewpoint of sufficiently obtaining the desired effect, the piezoelectric constant d 33 It is sufficient if the signal is less than 30 pC / N.

[0053] A piezoelectric film mainly made of fluororesin reacts with the volatile components of the transparent adhesive sheet and discolors. However, by using a transparent adhesive sheet that satisfies the above-mentioned condition 1, or both conditions 1 and 2, it is possible to obtain the effect that the piezoelectric film mainly made of fluororesin does not discolor. When a piezoelectric film mainly made of fluororesin is used, discoloration due to reaction with the volatile components is mainly yellowing.

[0054] (Layer structure of piezoelectric laminate film) The piezoelectric laminated film may have any layer other than the piezoelectric film and the transparent adhesive sheet. For example, it may have a transparent conductive layer, a transparent coating layer, a transparent substrate, etc. In addition, the material, thickness, number, etc. of the layer that is added arbitrarily are not particularly limited as long as they can be suitably used for the piezoelectric laminated film.

[0055] The transparent conductive layer may be a layer having a planar extension and a conductive structure, also called a transparent electrode. The transparent conductive layer is a layer having a thickness of about 10 nm or more and less than 45 nm. The form of the transparent conductive layer is not particularly limited, and may be a nanowire, a mesh, a thin film, or the like. The thin film may be a single layer or a laminated structure of multiple layers.

[0056] The material constituting the transparent conductive layer is not particularly limited, and a metal oxide of at least one metal selected from the group consisting of In, Sn, Zn, Ga, Sb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, and W is preferably used. The metal oxide may further contain a metal atom shown in the above group as necessary. As the metal oxide, ITO and antimony-tin composite oxide (ATO) are preferably used, and ITO is particularly preferably used. Other representative examples of materials for the transparent conductive layer include silver nanowires, silver mesh, copper mesh, graphene, and carbon nanotubes.

[0057] Examples of the transparent coating layer include a hard coat layer, an optical adjustment layer, and an undercoat layer. The transparent coating layer may be a single layer or a combination of multiple layers.

[0058] The hard coat layer is a transparent protective layer for the piezoelectric film that is widely used in piezoelectric laminate films to prevent the surface of the piezoelectric film from being scratched. The hard coat layer is a layer with a thickness of approximately 0.2 μm to 3 μm.

[0059] The material of the transparent coating layer is not particularly limited, and may be an inorganic material or an organic material, and may be one or more kinds. The material of the coating layer may be the material of the hard coat layer. Examples of the material include melamine resin, urethane resin, (meth)acrylic acid ester resin, epoxy resin, phenoxy resin, melamine resin, silane compound, and metal oxide. Note that "(meth)acrylic acid ester" is a general term for acrylic acid ester and methacrylic acid ester, and means one or both of them.

[0060] The transparent coating layer may have various functions within the range in which the effect of this embodiment is exhibited. The material of the transparent coating layer may further contain a material for exhibiting any function as another component. Examples of such materials include an optical adjuster for controlling the refractive index of the transparent coating layer, an antistatic agent, a silane coupling agent, and an antiblocking agent. Examples of the optical adjuster include inorganic particles and polymer beads, such as hollow silica-based fine particles, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, zinc oxide, and tin oxide. Examples of the antistatic agent include a surfactant, antimony pentoxide, indium tin oxide, and conductive polymers.

[0061] The transparent substrate may be provided as the outermost layer of the piezoelectric laminate film from the viewpoint of protecting the surface of the piezoelectric laminate film. The transparent substrate is not particularly limited as long as it is a substrate that can protect the surface of the piezoelectric laminate film and is transparent like a general optical film. Examples of materials for such a transparent substrate include transparent materials such as glass, polyethylene terephthalate, cycloolefin polymer, and polycarbonate. The transparent substrate may contain one or a mixture of these materials.

[0062] In addition to the above-mentioned layer configuration, other layer configurations may be included to improve the optical properties of the piezoelectric laminate film, such as an antiglare layer or an antireflection layer.

[0063] In addition, the optical film may further include a layer having a protective function, such as a known anti-smudge (anti-fingerprint) layer and a protective film layer.

[0064] The order of laminating each layer is not particularly limited. The piezoelectric film and the transparent adhesive sheet may be directly bonded. Such a piezoelectric laminate film may be a piezoelectric laminate film in which a transparent adhesive sheet and a protective film are laminated in this order on both sides of the piezoelectric film.

[0065] Also, another layer may be interposed between the piezoelectric laminate film and the transparent adhesive sheet. For example, a transparent coating layer may be provided between the piezoelectric film and the transparent adhesive sheet. Such a piezoelectric laminate film may include a piezoelectric laminate film in which a transparent coating layer, a transparent adhesive sheet, and a protective film are laminated in this order on both sides of the piezoelectric film. Even if another layer exists between the piezoelectric film and the transparent adhesive sheet, a change in color tone due to volatile substances may occur. Therefore, even if the piezoelectric film and the transparent adhesive sheet are laminated with another layer, the change in color tone at high temperatures can be suppressed by using a transparent adhesive sheet that satisfies the above-mentioned condition 1 or both conditions 1 and 2.

[0066] (Physical properties of piezoelectric laminate film) The piezoelectric laminate film of the present embodiment shows little change in color tone even when exposed to a high-temperature and high-humidity environment for a long period of time. * a * b * The evaluation can be performed using a color system. More specifically, the L * Value, a * value, and b * Furthermore, the change in color tone, ΔE, can be calculated using the following formula:

number

[0067] Here, ΔL * , Δa * , Δb * are the L of the piezoelectric laminate film that changed due to high temperature and high humidity environments. * Value, a * Value, b * It is the difference in values.

[0068] L of piezoelectric laminated film * The value is preferably 85 or more, and more preferably 90 or more. * The value is preferably -1 or more and 1 or less, and more preferably -0.5 or more and 0.5 or less. * The value may be from -5 to 5, preferably from -4 to 4, more preferably from -3 to 3, even more preferably from -2 to 2, and most preferably from -1 to 1. * Value, a * value, and b * If the value is within the range, it can be judged that there is no practical problem in applications such as touch panels. * When the value does not exceed the upper limit, it can be determined that the yellowing of the piezoelectric laminate film has been suppressed.

[0069] The value of ΔE, which indicates the color change of the piezoelectric laminate film caused by long-term exposure to a high-temperature, high-humidity environment, is preferably not more than 5, and more preferably not more than 3. If the color change of the piezoelectric laminate film before and after exposure to a high-temperature, high-humidity environment is within this range, it can be determined that no color change of the piezoelectric laminate film due to the high-temperature, high-humidity environment is observed.

[0070] In addition, the piezoelectric laminate film's b caused by long-term exposure to a high-temperature and high-humidity environment * Δb represents the change in value * The value of b is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less. *For piezoelectric laminate films with a value between -5 and 5, the Δb value of the piezoelectric laminate film before and after exposure to a high temperature and high humidity environment * When the value is within the range, it can be determined that yellowing of the piezoelectric laminate film due to a high-temperature and high-humidity environment is not observed.

[0071] In addition, ΔE and Δb * The closer to 0 the value, the better.

[0072] Here, exposure to a high temperature and high humidity environment for a long period of time means, for example, exposure to 85° C. and 85% RH for 1000 hours.

[0073] (Applications of piezoelectric laminated film) The piezoelectric laminate film according to the present embodiment may be used in a touch panel. By using the piezoelectric laminate film according to the present embodiment in a touch panel, a touch panel that can suppress discoloration even in a high-temperature and high-humidity environment can be obtained. In particular, a touch panel that can suitably suppress yellowing can be obtained.

[0074] The piezoelectric laminated film according to the present embodiment may be used in combination with an existing transparent electrode layer. The existing transparent electrode layer, for example, plays the role of a sensor for detecting a position. The existing transparent electrode layer may be, for example, a film containing one or more of polyethylene terephthalate (PET), cycloolefin polymer (COP), and polycarbonate (PC) as materials, to which a transparent conductive layer is laminated. The transparent conductive layer included in the existing transparent electrode layer is not particularly limited, and may be the same layer as the transparent conductive layer described above.

[0075] 2. Manufacturing method of piezoelectric laminate film A method for producing a piezoelectric laminate film according to one embodiment of the present invention includes a preparation step of preparing a transparent adhesive sheet that satisfies the following condition 1, and a lamination step of laminating the transparent adhesive sheet that satisfies the condition 1 and a piezoelectric film.

[0076] Condition 1: 1cm when held at 85℃ for 90 minutes2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the total amount of organic matter detected after a retention time of 3 minutes was 50 μg or less in terms of weight of 2,2'-azobis(isobutyronitrile).

[0077] In the method for producing a piezoelectric laminate film according to one embodiment of the present invention, the transparent adhesive sheet may further satisfy the following condition 2.

[0078] Condition 2: 1cm when held at 85℃ for 90 minutes 2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the amount of components attributed to bases and silane coupling agents detected after a retention time of 3 minutes was less than 15 μg, calculated as 2,2'-azobis(isobutyronitrile) by weight.

[0079] (preparation process) In the preparation step, a transparent adhesive sheet that satisfies the above-mentioned condition 1 or a transparent adhesive sheet that satisfies both conditions 1 and 2 is prepared. The preparation method is not limited, and for example, when the analysis shows that the transparent adhesive sheet used in the piezoelectric laminate film satisfies the above-mentioned condition 1 or both conditions 1 and 2, the transparent adhesive sheet can be used as it is for producing the piezoelectric laminate film.

[0080] When using a commercially available product, the transparent adhesive sheet is not particularly limited as long as it can be used as the transparent adhesive sheet of the piezoelectric laminated film. For example, LUCIACS CS986 series manufactured by Nitto Denko Corporation ("LUCIACS" is a registered trademark of Nitto Denko Corporation), NNX series manufactured by Gunze Co., Ltd., SANCUARY manufactured by Sanei Kaken Co., Ltd. ("SANCUARY" is a registered trademark of Sanei Kaken Co., Ltd.), Panaclean series manufactured by Panac Corporation ("Panaclean" is a registered trademark of Panac Corporation), and Opteria series manufactured by Lintec Corporation ("Opteria" is a registered trademark of Lintec Corporation) can be mentioned, but is not limited thereto.

[0081] Some commercially available transparent adhesive sheets can be used as transparent adhesive sheets for piezoelectric laminate films, but if untreated, they may not satisfy condition 1, or both conditions 1 and 2. For this reason, any treatment may be performed in the preparation step to produce a transparent adhesive sheet that satisfies condition 1, or both conditions 1 and 2.

[0082] Examples of treatments for obtaining a transparent adhesive sheet that satisfies the above-mentioned conditions 1 and 2 include heat treatment and cleaning treatment. Among them, heat treatment is preferable from the viewpoint of maintaining the adhesiveness of the transparent adhesive sheet.

[0083] For example, in the preparation step, a transparent adhesive sheet that does not satisfy condition 1 or does not satisfy both condition 1 and condition 2 may be heat-treated at 40°C to 135°C to volatilize the volatile components contained in the transparent adhesive sheet to obtain a transparent adhesive sheet that satisfies the above-mentioned conditions. In this specification, the symbol "to" indicates a range including both ends of the numerical value (above and below).

[0084] The heat treatment temperature for volatilizing the volatile components contained in the transparent adhesive sheet is preferably 40° C. to 135° C., and more preferably 60° C. to 85° C. When the heat treatment temperature is not lower than the lower limit, the volatile components can be sufficiently volatilized. Also, when the heat treatment temperature is not higher than the upper limit, deformation of the transparent adhesive sheet can be prevented.

[0085] The time of the heat treatment is not particularly limited as long as it is within a range in which the volatile components contained in the transparent adhesive sheet can be volatilized. For example, the time of the heat treatment is preferably 1 minute or more, more preferably 3 minutes or more, and even more preferably 5 minutes or more. By setting the time of the heat treatment not below the lower limit, the volatile components can be sufficiently volatilized. In addition, the time of the heat treatment is preferably 24 hours or less, more preferably 12 hours or less, even more preferably 6 hours or less, and particularly preferably 1 hour or less. By setting the time of the heat treatment not above the upper limit, the time required for the preparation process can be shortened.

[0086] Such a heat treatment may be performed, for example, at 85° C. for 24 hours.

[0087] By preparing a transparent adhesive sheet that satisfies condition 1 or both conditions 1 and 2 in the preparation step, even a transparent adhesive sheet that does not satisfy condition 1 or both conditions 1 and 2 can be used suitably.

[0088] (Lamination process) The lamination step is not particularly limited as long as the transparent adhesive sheet and the piezoelectric film can be laminated to produce a piezoelectric laminate film. The transparent adhesive sheet and the piezoelectric film may be laminated so as to be in direct contact with each other, or may be laminated via another layer.

[0089] For example, a transparent adhesive sheet may be laminated on both sides of a piezoelectric film, and a transparent substrate may be laminated on both sides of the piezoelectric film. Alternatively, a transparent coating layer may be laminated on both sides of a piezoelectric film, and a transparent adhesive sheet may be laminated on both sides of the transparent coating layer, and a transparent substrate may be laminated on both sides of the transparent coating layer.

[0090] The method for laminating each layer may be according to a conventionally known method. The transparent adhesive sheet can be laminated by sticking it to the piezoelectric film. The transparent substrate can be laminated, for example, by a laminator. The transparent coating layer can be coated and laminated, for example, by a bar coater.

[0091] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.

[0092] (summary) The present invention can also be expressed as follows.

[0093] The piezoelectric laminate film according to the present embodiment 1 is composed of a piezoelectric film and a transparent adhesive sheet, and the transparent adhesive sheet satisfies the following condition 1. Condition 1: 1cm when held at 85℃ for 90 minutes 2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the total amount of organic matter detected after a retention time of 3 minutes was 50 μg or less in terms of weight of 2,2'-azobis(isobutyronitrile).

[0094] This configuration makes it possible to provide a piezoelectric laminate film whose color tone does not change even in a high-temperature and high-humidity environment.

[0095] In addition, the piezoelectric laminate film according to the present embodiment is a transparent adhesive sheet according to the embodiment 1, further satisfying the following condition 2. Condition 2: 1cm when held at 85℃ for 90 minutes 2When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the amount of components attributed to bases and silane coupling agents detected after a retention time of 3 minutes was less than 15 μg, calculated as 2,2'-azobis(isobutyronitrile) by weight.

[0096] This configuration can reduce the amount of volatile substances originating from the transparent adhesive sheet, which changes the color tone of the piezoelectric film in a high-temperature and high-humidity environment.

[0097] Furthermore, the piezoelectric laminated film according to the present embodiment is the piezoelectric film of the embodiment 1, which contains a fluorine-based resin as a main component.

[0098] Furthermore, the piezoelectric laminate film according to the present embodiment 4 is the piezoelectric film of the embodiment 2, wherein the piezoelectric film contains a fluorine-based resin as a main component. In the case of the above-mentioned embodiment 3 or 4, the amount of volatile components from the transparent adhesive sheet is small, and the reaction with the fluorine-based resin can be suppressed, so that yellowing of the piezoelectric film can be prevented.

[0099] The manufacturing method of this embodiment 5 is a method for manufacturing a piezoelectric laminated film, including a preparation step of preparing a transparent adhesive sheet that satisfies the following condition 1, and a lamination step of laminating the transparent adhesive sheet that satisfies the condition 1 and a piezoelectric film. Condition 1: 1cm when held at 85℃ for 90 minutes 2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the total amount of organic matter detected after a retention time of 3 minutes was 50 μg or less in terms of weight of 2,2'-azobis(isobutyronitrile).

[0100] This configuration makes it possible to produce a piezoelectric laminate film whose color tone does not change even in a high-temperature and high-humidity environment.

[0101] The manufacturing method of this aspect 6 is the manufacturing method described in claim 4, which includes, in the above-mentioned aspect 5, a preparation step of preparing a transparent adhesive sheet that satisfies the following condition 2, and a lamination step of laminating the transparent adhesive sheet that satisfies the condition 2 and a piezoelectric film. Condition 2: 1cm when held at 85℃ for 90 minutes 2 When the volatile components obtained from each test piece were subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the amount of components attributed to bases and silane coupling agents detected after a retention time of 3 minutes was less than 15 μg, calculated as 2,2'-azobis(isobutyronitrile) by weight.

[0102] This configuration makes it possible to produce a piezoelectric laminate film whose color tone does not change even in a high-temperature and high-humidity environment.

[0103] The production method according to the present embodiment 7 is a method for producing a piezoelectric laminate film, in which in the preparation step, a transparent adhesive sheet that does not satisfy the above condition 1 or does not satisfy both the above conditions 1 and 2 is heat-treated at 40° C. to 135° C. to obtain a transparent adhesive sheet that satisfies the above condition 1 or both conditions 1 and 2. With this configuration, even in a transparent adhesive sheet with a high volatile component content, the volatile component can be suppressed, so that a transparent adhesive sheet that is preferable as a material for a piezoelectric laminate film can be prepared.

[0104] The manufacturing method of aspect 8 is a method for manufacturing a piezoelectric laminate film, in which in the preparation step of aspect 6, a transparent adhesive sheet that does not satisfy both of the above conditions 1 and 2 is heat-treated at 40°C to 135°C to obtain a transparent adhesive sheet that satisfies both conditions 1 and 2.

[0105] The touch panel according to the present embodiment 8 is a touch panel including the piezoelectric laminate film according to any one of the embodiments 1 to 4. This configuration makes it possible to provide a touch panel that does not discolor even under high temperature and high humidity conditions.

[0106] [Example] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0107] 1. Production of Piezoelectric Laminated Film <Example 1> (Preparation of piezoelectric film) Polyvinylidene fluoride (inherent viscosity 1.1 dl / g) was melt-molded into a sheet with a thickness of 140 μm and a width of 350 mm, which was then uniaxially stretched by about 4.1 times to obtain a uniaxially stretched film. A direct current voltage of 11.8 kV was applied to the uniaxially stretched film to perform a polarization treatment, and then the film was heat-treated at 130° C. for 40 seconds to obtain a piezoelectric film with a thickness of 40 μm.

[0108] (Lamination of transparent adhesive sheets) A commercially available substrate-less transparent adhesive sheet A (thickness 25 μm) whose main component is butyl acrylate was cut into A4 size and one side of the release sheets attached to both sides was peeled off, and then the sheet was attached to one side of the above-mentioned piezoelectric film at a pressure of 0.2 MPa using a Halder laminator (MRK-650Y Halder Laminator, manufactured by MCK Corporation). The same operation was performed on the other side of the piezoelectric film to obtain a piezoelectric laminate film in which a transparent adhesive layer was formed on both sides of the piezoelectric film.

[0109] <Example 2> (Preparation of piezoelectric film) In the same manner as in Example 1, a piezoelectric film was obtained.

[0110] (Heat treatment of transparent adhesive sheets) A commercially available substrate-less transparent adhesive sheet B (thickness 50 μm), whose main adhesive component is 2-hexylethyl acrylate, was cut to A4 size, and one of the release sheets attached to both sides was peeled off. The sheet was then heated at 85°C for 24 hours in a gear oven (GPS-60H, manufactured by Shimizu Rikagaku Kikai Seisakusho Co., Ltd.) to obtain a transparent adhesive sheet D.

[0111] (Lamination of transparent adhesive sheet D) The obtained transparent adhesive sheet D was attached to a piezoelectric film in the same manner as in Example 1 to obtain a piezoelectric laminate film.

[0112] <Example 3> (Preparation of piezoelectric film) A piezoelectric film was obtained in the same manner as in Example 1. An amorphous silica-containing ultraviolet-curable resin composition (material) made of an acrylic resin was applied to both sides of the piezoelectric film, dried at 60°C, and then irradiated with ultraviolet light to form a hard coat layer having a thickness of 1 μm, thereby producing a piezoelectric film provided with a hard coat layer.

[0113] (Lamination of transparent adhesive sheets) The transparent adhesive sheet A was attached to the piezoelectric film in the same manner as in Example 1 to obtain a piezoelectric laminate film.

[0114] <Comparative Example 1> The same procedure as in Example 1 was carried out except that the transparent adhesive sheet B was used instead of the transparent adhesive sheet A.

[0115] <Comparative Example 2> The same procedure as in Example 1 was repeated, except that transparent adhesive sheet A was replaced with a commercially available substrate-less transparent adhesive sheet C (thickness 75 μm) different from transparent adhesive sheet B, the main adhesive component of which was 2-hexylethyl acrylate.

[0116] (Piezoelectric constant d 33 ) The piezoelectric constants d of the laminated piezoelectric films of Examples 1 to 3 and Comparative Examples 1 and 2 33 The piezoelectric constant was measured using a piezoelectric constant measuring device (Piezometer System PM300, manufactured by PIEZOTEST). The conditions for measuring the piezoelectric constant were as follows:

[0117] (Measurement conditions for piezoelectric constant) Static Force: 0.2N Oscillation Force: 0.15N Frequency: 110Hz Measurement Range: Low Probe: Small domed electrode

[0118] The voltage (d 33 ), the presence or absence of a transparent coating layer, and the type of transparent adhesive sheet are shown in Table 1. [Table 1]

[0119] 2. Evaluation of Piezoelectric Laminated Film <High temperature and humidity environment test> The piezoelectric laminated films produced in Examples 1 to 3 and Comparative Examples 1 and 2 were cut into squares with sides of 10 cm to prepare test pieces. The test pieces were placed in a thermo-hygrostat (Econas LH34-14M, manufactured by Nagano Science Co., Ltd.) set to 85°C and 85% RH to conduct a high-temperature, high-humidity environmental test. The test pieces were removed 1000 hours after the start of the high-temperature, high-humidity environmental test. The color tone of each test piece before and after the high-temperature, high-humidity environmental test was measured according to the following conditions to evaluate the color tone change due to the high-temperature, high-humidity environment.

[0120] (Evaluation of color tone and color tone change) The color tone of the piezoelectric laminate film is L * a * b * The evaluation was carried out using a color system. Using a spectrophotometer (SE7700 manufactured by Nippon Denshoku Industries Co., Ltd.), the L * Value, a * value, and b * Specifically, the measurement was performed using a transmission method under geometric conditions (0°:0°) with D65 / 10° as the measurement light. The ΔE value, which represents the change in color tone, was calculated using the following formula.

number

[0121] Here, ΔL * , Δa * , Δb *are the L of the piezoelectric laminate film before and after the high temperature and high humidity environment test, respectively. * Value, a * Value, b * It is the difference in values.

[0122] In addition, the L of the piezoelectric laminate film * A value of 85 or more is preferable, and a value of 90 or more is more preferable. * The value is preferably greater than or equal to -1 and less than or equal to 1, and more preferably greater than or equal to -0.5 and less than or equal to 0.5. * The value is preferably -5 or more and 5 or less, and more preferably -4 or more and 4 or less. * Value, a * value, and b * If the value is within the range, it can be determined that there is no practical problem in the use of devices such as touch panels.

[0123] The color change (ΔE) of the piezoelectric laminate film before and after the high temperature and high humidity environmental test is preferably not more than 5, and more preferably not more than 3. When the ΔE value is within this range, it can be determined that no color change is observed in the piezoelectric laminate film.

[0124] In particular, the b before and after the high temperature and high humidity environment test * Δb represents the change in value * The value of is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less. * For piezoelectric laminated films with values ​​between -5 and 5, Δb before and after high temperature and high humidity environmental testing * When the value is within the range, it can be determined that yellowing of the piezoelectric laminate film due to a high-temperature and high-humidity environment is not observed.

[0125] The changes in color tone of each test piece due to the high temperature and high humidity environmental test are shown in the following Table 2. Note that all of the color changes in the test pieces were due to the piezoelectric film, and not due to the transparent adhesive sheet.

[0126] [Table 2]

[0127] <Total amount of volatile substances generated from transparent adhesive sheets> The total amount of volatile substances generated from the transparent pressure-sensitive adhesive sheets A to D in a high-temperature environment was determined by solid-phase microextraction and gas chromatography mass spectrometry. Specifically, the total amount of volatile substances was determined as follows.

[0128] The release sheets on both sides of the transparent adhesive sheets A to D cut into squares with sides of 2.5 cm were removed, and the transparent adhesive sheets A to D were separated and attached to the lower part of the inner wall of a vial tube (Screw vials with flat top 20 ml Clear glass, manufactured by Gerstel), and plugged with a septum (silicone rubber / PTFE) and a screw cap. After that, the vial tube was heated at 85°C for 30 minutes using an agitator attached to an autosampler (Multipurpose Sampler MPS2, manufactured by Gerstel), and then a fiber for SPME (solid phase microextraction) (PDMS, manufactured by Sigma-Aldrich; poly dimethyl siloxane coating, film thickness: 100 μm) was inserted into the vial tube and the volatile substances were adsorbed onto the fiber at 85°C for 60 minutes. The fiber was inserted into the injection port of a gas chromatograph mass spectrometer (Agilent GC7890A / MS5975C) and heated at 250°C for 30 seconds to desorb the adsorbed volatile substances. The total ion chromatogram (TIC) was obtained by measuring the amount of the adsorbed volatile substances under the gas chromatograph mass spectrometry conditions described below.

[0129] (Gas chromatograph mass spectrometry conditions) Equipment used GC / MS: Agilent GC7890A / MS5975C Autosampler: Gerstel MultiPurpose Sampler MPS2 Vials: Gerstel Screw vials with flat top 20ml Clear glass, for 18 mm-screw caps Septum cover: Gerstel septum (Sillicone / PTFE) Art.-Nr.: 093640-057-00

[0130] GC section conditions Column: GL Sciences TC-17 30m x 250μm x 0.25μm Oven program: 40℃×5min-20℃ / min-250℃×10min Injection method: splitless Heater temperature: 250℃ Column flow rate: 1mL / min Carrier gas: He Purge flow rate to split vent: 50mL / min Start time: 1min Initial solvent removal time: 3 min

[0131] MS conditions Ionization method: EI Ion source temperature: 230℃ ·Quadrupole temperature: 150℃

[0132] Furthermore, chloroform solutions of different concentrations were prepared using 2,2'-azobis(isobutyronitrile) (Wako Special Grade, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a standard sample, and 5 μL of each solution was weighed out and the gas chromatogram was measured in the same manner as for the transparent adhesive sheet. A calibration curve was created from the peak area in the obtained TIC and the amount of 2,2'-azobis(isobutyronitrile) added, and the total amount of volatile components generated from the transparent adhesive sheet was calculated in weight in terms of 2,2'-azobis(isobutyronitrile) from this calibration curve and the total peak area of ​​the TIC of the transparent adhesive sheet. The total amount of the obtained volatile substances was multiplied by the surface area (6.25 cm2) of the transparent adhesive sheet. 2 ) to get 1cm 2 The weight of the volatile components evaporated from the transparent pressure-sensitive adhesive sheets A to D is shown in Table 3 below. [Table 3]

[0133] <Amount of volatile components generated from transparent adhesive sheet> The areas of the peaks attributable to the basic substances and the silane coupling agents were determined individually, and the weights were calculated in terms of 2,2'-azobis(isobutyronitrile) using the calibration curve obtained above. The compounds attributable to the basic substances and the silane coupling agents in each sheet are shown below.

[0134] Transparent adhesive sheet A: No compounds that could be attributed to basic substances or silane coupling agents were found.

[0135] Transparent adhesive sheet B: N-vinyl-2-pyrrolidone and 3-glycidyloxypropyltrimethoxysilane, which appeared at retention times of 11.71 minutes and 13.53 minutes, respectively, were assigned to a basic substance and a silane coupling agent, respectively, and were calculated from the respective peak areas.

[0136] Transparent adhesive sheet C: Diacetone acrylamide and trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, which appeared at retention times of 12.57 minutes and 14.44 minutes, respectively, were assigned to a basic substance and a silane coupling agent, respectively, and were calculated from their respective peak areas.

[0137] Transparent adhesive sheet D: No compounds attributed to basic substances or silane coupling agents were found.

[0138] 3. Coloring of piezoelectric film by volatile substances in transparent adhesive sheet (Experimental Example 1) Water (100 mL) was placed in a vial, and 100 mmol of N-methyl-2-pyrrolidone was added and stirred to form a homogeneous solution. A piezoelectric film test piece cut into a 5 cm square was immersed in the solution. The vial was then capped and placed in an oven at 85°C to carry out a high-temperature, high-humidity environmental test. The color tone of the test piece was evaluated 100 hours after the start of the high-temperature, high-humidity environmental test.

[0139] (Experimental Example 2) A high-temperature, high-humidity environmental test was carried out in the same manner as in Experimental Example 1, except that N-methyl-2-pyrrolidone was not added to the vial.

[0140] (Experimental Example 3) A high temperature and high humidity environmental test was carried out in the same manner as in Experimental Example 1, except that 100 mL of toluene was used instead of water as the solvent added to the vial, and 3-glycidyloxypropyltrimethoxysilane was used as the solvent instead of N-methyl-2-pyrrolidone.

[0141] (Experimental Example 4) A high-temperature, high-humidity environmental test was carried out in the same manner as in Experimental Example 3, except that 3-glycidyloxypropyltrimethoxysilane was not added to the vial tube.

[0142] (Evaluation of color tone and color tone change) L of the test pieces after high temperature and high humidity environmental tests in Experimental Examples 1 to 4 * Value, a * Value, b * The L value was measured in the same manner as in the evaluation of the color tone and color tone change of the piezoelectric film shown in [2. Evaluation of the piezoelectric laminate film]. * The value is 96.6, a * The value is 0.1, b * The value was 0.8. The measurement results of the color tone and color tone change of the piezoelectric film are shown in Table 4 below. [Table 4]

[0143] From Table 4, it was found that the piezoelectric film to which the volatile substances in the transparent adhesive sheet and similar compounds were added turned yellow when subjected to a high-temperature and high-humidity environmental test. [Industrial Applicability]

[0144] The present invention can be used for a touch panel or the like.

Claims

1. It is composed of a piezoelectric film and a transparent adhesive sheet, The piezoelectric laminate film, wherein the transparent adhesive sheet satisfies the following condition 1: Condition 1: 1 cm when held at 85°C for 90 minutes 2 When the volatile components obtained from the test piece per unit area are subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the total amount of organic matter detected after a retention time of 3 minutes is 50 μg or less in terms of the weight of 2,2'-azobis(isobutyronitrile).

2. The piezoelectric laminate film according to claim 1 , wherein the transparent adhesive sheet further satisfies the following condition 2: Condition 2: 1 cm when held at 85°C for 90 minutes 2 When the volatile components obtained from the test piece per unit area were subjected to solid phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the amount of components attributed to the base and silane coupling agent detected after a retention time of 3 minutes was less than 15 μg in terms of the weight of 2,2'-azobis(isobutyronitrile).

3. The piezoelectric laminate film according to claim 1 , wherein the piezoelectric film contains a fluorine-based resin as a main component.

4. The piezoelectric laminate film according to claim 2 , wherein the piezoelectric film contains a fluorine-based resin as a main component.

5. A method for producing a piezoelectric laminated film, comprising: a preparation step of preparing a transparent adhesive sheet that satisfies the following condition 1; and a lamination step of laminating the transparent adhesive sheet that satisfies the condition 1 and a piezoelectric film. Condition 1: 1 cm when held at 85°C for 90 minutes 2 When the volatile components obtained from the test piece per unit area are subjected to solid-phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the total amount of organic matter detected after a retention time of 3 minutes is 50 μg or less in terms of the weight of 2,2'-azobis(isobutyronitrile).

6. The method for producing a piezoelectric laminate film according to claim 5 , wherein the transparent adhesive sheet further satisfies the following condition 2: Condition 2: 1 cm when held at 85°C for 90 minutes 2 When the volatile components obtained from the test piece per unit area were subjected to solid phase microextraction, adsorbed onto a fiber coated with polydimethylsiloxane, and analyzed by a gas chromatograph mass spectrometer, the amount of components attributed to the base and silane coupling agent detected after a retention time of 3 minutes was less than 15 μg in terms of the weight of 2,2'-azobis(isobutyronitrile).

7. The method for producing a piezoelectric laminate film described in claim 5, wherein in the preparation step, a transparent adhesive sheet that does not satisfy the condition 1 is heat-treated at 40°C to 135°C to obtain a transparent adhesive sheet that satisfies the condition 1.

8. The method for producing a piezoelectric laminate film described in claim 6, wherein in the preparation step, a transparent adhesive sheet that does not satisfy both of the above conditions 1 and 2 is heat-treated at 40°C to 135°C to obtain a transparent adhesive sheet that satisfies both conditions 1 and 2.

9. A touch panel comprising the piezoelectric laminate film according to claim 1 .

Citation Information

Patent Citations

  • Method for manufacturing transparent piezoelectric panel

    JP2015075968A

  • Adhesive tape and manufacturing method therefor

    JP2017105878A

  • Touch panel

    WO2013021835A1

  • Piezoelectric film

    WO2015064328A1

  • Touch panel and electronic device

    WO2015156196A1